1981
DOI: 10.1007/bf00434394
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic study of cerebrospinal fluid penetration of cis-diamminedichloroplatinum (II)

Abstract: The ability of cis-DDP and several analogs to enter the CSF was investigated in rhesus monkeys that had subcutaneously implanted Ommaya reservoirs connected to catheters in each monkey's fourth ventricle. Plasma and CSF samples were analyzed for platinum content by atomic absorption spectroscopy. Plasma platinum curves were biphasic with a very slowly declining terminal phase. CSF platinum curves rose to maximum concentrations 30-40 min after an IV bolus injection and declined mono-exponentially (T 1/2 = 60 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

1983
1983
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 6 publications
1
6
0
Order By: Relevance
“…The CSF penetration of cisplatin in our model is similar to a prior study (18), but the CSF penetration of carboplatin is lower than previous reports (8 -10). The disparity between our study and these previous reports with carboplatin may be related to the limited number CSF samples measured in prior studies.…”
Section: Discussionsupporting
confidence: 86%
“…The CSF penetration of cisplatin in our model is similar to a prior study (18), but the CSF penetration of carboplatin is lower than previous reports (8 -10). The disparity between our study and these previous reports with carboplatin may be related to the limited number CSF samples measured in prior studies.…”
Section: Discussionsupporting
confidence: 86%
“…The highest concentrations are found in the kidneys, liver, ovaries, uterus, and prostate gland (LeRoy et al 1979;Stewart et al 1982a). Low concentrations are achieved in cerebrospinal fluid, indicating poor penetration into the central nervous system (Gormley et al 1981). However, cisplatin may selectively distribute into intracerebral tumours, and has been reported to have antitumour activity for central nervous system neoplasms (Stewart et al…”
Section: Distributionmentioning
confidence: 96%
“…However, according to another study [15], CDDP penetrates the cerebrospinal fluid space at a rate of 2.5 % of the maximum plasma concentration when administered intravenously at high doses. We found that 30-40% of the drug at tumor level is distributed in the brain adjacent to the tumor site, where the blood-brain barrier is intact, when high doses (100mg/sq m) are administered intravenously (Nakagawa et al, submitted for publication).…”
Section: Discussionmentioning
confidence: 97%